2013
DOI: 10.1177/156482651303400206
|View full text |Cite
|
Sign up to set email alerts
|

Using Program Impact Pathways to Understand and Improve Program Delivery, Utilization, and Potential for Impact of Helen Keller International's Homestead Food Production Program in Cambodia

Abstract: Background. Evidence of the impact of homestead food production programs on nutrition outcomes such as anemia and growth is scant. In the absence of information on program impact pathways, it is difficult to under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 8 publications
1
62
0
1
Order By: Relevance
“…Our study contributes to a growing body of implementation research using varied and rigorous methods to assess how well nutrition programmes are delivered and utilized compared to plans (Avula et al, ; Kim et al, ; M. N. N. Mbuya et al, ; Menon, Rawat, & Ruel, ; Rajaraman et al, ), how to optimize programme implementation (Olney, Vicheka, et al, ; Winch et al, ) and to provide confirmatory evidence of the posited causal pathways (Loechl et al, ; Robert et al, ). Like ours, other studies have identified breakdowns in the pathway between training and effective application of its contents, including the volume of content to be absorbed, the skills and attributes of trainers, logistical and human challenges to adequate supervision, and the considerable and perhaps unrealistic demands placed on community agents (Kim et al, ; Mbuya, Menon, Habicht, Pelto, & Ruel, ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Our study contributes to a growing body of implementation research using varied and rigorous methods to assess how well nutrition programmes are delivered and utilized compared to plans (Avula et al, ; Kim et al, ; M. N. N. Mbuya et al, ; Menon, Rawat, & Ruel, ; Rajaraman et al, ), how to optimize programme implementation (Olney, Vicheka, et al, ; Winch et al, ) and to provide confirmatory evidence of the posited causal pathways (Loechl et al, ; Robert et al, ). Like ours, other studies have identified breakdowns in the pathway between training and effective application of its contents, including the volume of content to be absorbed, the skills and attributes of trainers, logistical and human challenges to adequate supervision, and the considerable and perhaps unrealistic demands placed on community agents (Kim et al, ; Mbuya, Menon, Habicht, Pelto, & Ruel, ).…”
Section: Discussionmentioning
confidence: 86%
“…The objectives were fourfold: (a) investigate if implementation and utilization were proceeding as designed; (b) evaluate the quality of programme activities; (c) invite feedback for improvements from beneficiaries and implementers; and (d) identify ways to strengthen delivery and/or utilization of the programme components to increase ultimate impact. The design and analysis of the PE were guided by the PIP model adapted from a version jointly designed by IFPRI, HKI, and local stakeholders for HKI's programme in Cambodia (Olney, Richter, et al, ; Figure ). The model distinguishes aspects of programme delivery and utilization and highlights three pathways to impact, each of which required contributions from the government as well as APRG and HKI: Improved production: VFL are trained and equipped to apply more productive cultivation techniques and to transfer these skills to beneficiary women producing at the household level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past few years, randomized controlled trials (RCTs) have investigated the evidence for a range of nutrition‐sensitive agricultural interventions, such as biofortification and improved and diversified household food production. These studies have demonstrated improvements in diet quality, micronutrient intake, and women's knowledge and empowerment by combining agricultural interventions, gender empowerment, and nutrition education …”
Section: Links Between Agriculture Food and Health In The Food Systemmentioning
confidence: 99%
“…2,3 It is theorized that by equipping women farmers with inputs and educational resources, technical assistance, and behaviour change communication (BCC), families will enjoy year round access to nutritious food thereby improving indicators of nutrition and food security of women and their young children. 3 To test this hypothesis in Cambodia and assess the impact of EHFP model at improving food security, nutrition outcomes, and women's empowerment, we conducted a cluster randomized controlled trial (RCT) from 2011 to 2014 known as Fish on Farms (FOF). In FOF, 900 households were randomly assigned to one of three arms: 1) EHFP (gardens only); 2) EHFP+F (gardens plus small pond aquaculture); or 3) control.…”
mentioning
confidence: 99%